Effectiveness of School Management through Strengthening the Managerial Ability of School Principals in the Field of Education Financing - Widyatmike Gede Mulawarman; Heriman Heriman; Prima Adi Pratama (PT ARRUS Intelektual Indonesia, 2022)
Along with the demands of an autonomous environment, it has an impact on the condition of schools that are increasingly competitive. Good management of education costs optimizes school functions to be more efficient and effective so as to improve school performance, quality and competitiveness. The results of the author's observations by observing several complaints from educators in designing activity programs to improve the quality of education require critical educational activities for educators and principals about education finance management. By using the workshop method, it is hoped that the objectives of this PKM activity are (1) providing knowledge to educators in preparing programs according to the education budget and (2) Providing skills in managing education budgets. This activity is designed offline whenever possible in the Meeting Hall at SDN 004 Bontang City and online if participants from outside Bontang City are not possible (during the COVID-19 Pandemic) to be carried out using the Zoom application. The methods used are explanatory methods, demonstrations and practices by means of seeding and questioning. The implementation of activities is carried out by providing material on strategic management of program preparation. The expected result in this training is that all skilled educators develop a program of activities with the preparation of the right budget